1991
DOI: 10.1093/ajcn/53.6.1431
|View full text |Cite
|
Sign up to set email alerts
|

Psyllium fiber reduces rise in postprandial glucose and insulin concentrations in patients with non-insulin-dependent diabetes

Abstract: The ability of psyllium fiber to reduce postprandial serum glucose and insulin concentrations was studied in 18 non-insulin-dependent diabetic patients in a crossover design. Psyllium fiber or placebo was administered twice during each 15-h crossover phase, immediately before breakfast and dinner. No psyllium fiber or placebo was given at lunch, which allowed measurement of residual or second-meal effects. For meals eaten immediately after psyllium ingestion, maximum postprandial glucose elevation was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 18 publications
2
53
1
6
Order By: Relevance
“…This result is similar to that obtained by Jarjis et al (1984) in healthy and in type 2 diabetic volunteers. Pastors et al (1991) found significant decreases for insulin after the administration of psyllium in type 2 diabetic patients, with a reduction (12%) higher than the reported in this study (5%). We have also found in a previous study (Sierra et al, 2001) carried out in healthy volunteers, a significant and higher reduction of insulin concentrations (36.1%) after the administration of ispaghula husk.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…This result is similar to that obtained by Jarjis et al (1984) in healthy and in type 2 diabetic volunteers. Pastors et al (1991) found significant decreases for insulin after the administration of psyllium in type 2 diabetic patients, with a reduction (12%) higher than the reported in this study (5%). We have also found in a previous study (Sierra et al, 2001) carried out in healthy volunteers, a significant and higher reduction of insulin concentrations (36.1%) after the administration of ispaghula husk.…”
Section: Discussioncontrasting
confidence: 86%
“…In contrast, no significant differences were found after a 50 g glucose load Therapeutic effects of psyllium M Sierra et al administered with 3.5 or 7 g fibre to healthy subjects (Jarjis et al, 1984). The mean decrease of C max obtained in this study after the administration of psyllium (10%) was similar to that reported by Sartor et al (1981) after a standardized breakfast (9%), and lower than the indicated by Pastors et al (1991) at breakfast (14%) and at dinner (20%), and by Sierra et al (2001) in healthy subjects after a glucose load (15.5%).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Psyllium in a supplemental drink form, has been specifically shown to lower postprandial glycemia in individuals with Type 2 DM when consumed just before a meal (Anderson et al, 1999;Sierra et al, 2002) and to have a residual effect after a second meal (Pastors et al, 1991;Anderson et al, 1999). Few studies have examined second meal responses to soluble fiber (Pastors et al, 1991;Sierra et al, 2002), but there is limited data on glycemic load and soluble fiber in influencing Type 2 DM (Salmeron et al, 1997;Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%